Effects of oral contraceptives on spatial cognition depend on pharmacological properties and phase of the contraceptive cycle - Hampson, Elizabeth; Morley, Erin E.; Evans, Kelly L.; Fleury, Cathleen (Frontiers in Endocrinology, 2022)
The central nervous system effects of oral contraceptives (OCs) are not well-documented. In a set of 3 studies we investigated a specific cognitive function, mental rotation, in healthy women currently using OCs for contraceptive purposes (n = 201) and in medication-free controls not using OCs (n = 44). Mental rotation was measured using a well-standardized and extensively validated psychometric test, the Vandenberg Mental Rotations Test (MRT). In an initial study (Study 1), current OC users (n = 63) were tested during the active or inactive phases of the contraceptive cycle in a parallel-groups design. Studies 2 and 3 were based on an archival dataset (n = 201 current OC users) that consisted of data on the MRT collected in real-time over a 30-year period and compiled for purposes of the present work. The OCs were combined formulations containing ethinyl estradiol (10-35 ug/day) plus a synthetic progestin. All 4 families of synthetic progestins historically used in OCs were represented in the dataset. Cognitive performance was evaluated during either active OC use (‘active phase’) or during the washout week of the contraceptive cycle (‘inactive phase’) when OC steroids are not used. The results showed a significant phase-of-cycle (POC) effect. Accuracy on the MRT was mildly diminished during the active phase of OC use, while scores on verbal fluency and speeded motor tasks were modestly improved. The POC effect was most evident in women using OCs that contained first- or second-generation progestins (the estrane family of progestins or OCs containing levonorgestrel), but not in women using OCs containing recently developed progestins and lower doses of ethinyl estradiol. Using independently established ratings of the estrogenic, androgenic, and progestogenic intensities of the different OC formulations, each brand of OC was classified according to its distinct endocrine profile. Multiple regression revealed that the effects of OC use on the MRT could be predicted based on the estrogenic strength of the contraceptives used. Estrogenic potency, not androgenic or anti-androgenic effects of the OC pill, may underlie the effects of OC usage on spatial cognition.